Expression of the purine biosynthetic enzyme phosphoribosyl formylglycinamidine synthase in neurons. Issue 6 (26th March 2018) - Mangold, Colleen A.; Yao, Pamela J.; Du, Mei; Freeman, Willard M.; Benkovic, Stephen J.; Szpara, Moriah L.
Abstract: Purines are metabolic building blocks essential for all living organisms on earth. De novo purine biosynthesis occurs in the brain and appears to play important roles in neural development. Phosphoribosyl formylglycinamidine synthase (FGAMS, also known as PFAS or FGARAT), a core enzyme involved in the de novo synthesis of purines, may play alternative roles in viral pathogenesis. To date, no thorough investigation of the endogenous expression and localization of de novo purine biosynthetic enzymes has been conducted in human neurons or in virally infected cells. In this study, we characterized expression of FGAMS using multiple neuronal models. In differentiated human SH‐SY5Y neuroblastoma cells, primary rat hippocampal neurons, and in whole‐mouse brain sections, FGAMS immunoreactivity was distributed within the neuronal cytoplasm. FGAMS immunolabeling in vitro demonstrated extensive distribution throughout neuronal processes. To investigate potential changes in FGAMS expression and localization following viral infection, we infected cells with the human pathogen herpes simplex virus 1. In infected fibroblasts, FGAMS immunolabeling shifted from a diffuse cytoplasmic location to a mainly perinuclear localization by 12 h post‐infection. In contrast, in infected neurons, FGAMS localization showed no discernable changes in the localization of FGAMS immunoreactivity. There were no changes in total FGAMS protein levels in either cell type. Together, these data provide insight into potential purine biosynthetic mechanisms utilized within neurons during homeostasis as well as viral infection. Cover Image for this Issue: doi:10.1111/jnc.14169 . Abstract : We examined expression and localization of the de novo purine biosynthetic enzyme, phophoribosyl formylglycinamidine (FGAMS), in multiple species and neuronal models. We found that endogenous FGAMS is localized throughout neuronal processes and near mitochondria, and is often found in proximity to synapses. These data provide insight into the mechanisms of purine metabolism in neurons. Cover Image for this Issue: doi:10.1111/jnc.14169 .